Literatura, fatalidade e história: o jornalismo engajado de José do Patrocínio (1877-1905) - Motta, Felipe Ronner Pinheiro Imlau (2008)
The aim of this research is to analyze the processes of creation in means of communication by José Carlos do Patrocínio, including his political performance, during the last years from XIXth century and the first ones from the XXth. Patrocínio was immortalized and placed to an important position among Brazilian History Studies by his engagement in defending the end of slavery. He has written many articles about the political life of the Brazilian Imperial Court and some more about the first years of the republican system. The journalist has worked in Gazeta de Notícias , one of the main periodics from Rio de Janeiro, in which masthead he has published his first two novels and where he has spent some time working, just leaving to found and manage his own newspaper, Cidade do Rio . That was a communication company where important names as Olavo Bilac and Coelho Neto have worked. The engagement of the journalist had taken him progressively to the stage and to a direct contact with the crowd. The central problem of this research is what we have called curse of engagement , due to the fact that Patrocínio, in spite of also being an important novelist, orator and journalist, was imprisoned in a place of memories where his professional life was reduced only to his political performance. That movement rejected to a second position his journalistic texts that are not about the subject of slavery. Like seeing things from a different point of view, we analyzed through the thesis the strategies used by the journalist in the coverage of the drought occurred in the Brazilian State of Ceará from 1877 to 1880. During those years, he wrote some articles and renewed the style adopted by the contemporary newspapers, by using pictures as a journalistic document for the first time in Brazil. He crowned the coverage of the drought by publishing a novel-serial in the masthead of Gazeta de Notícias and its reading reveals his most creative attitude: his journalistic performance and the artistic aspects involved. This creative journalism was despised by the memory of the engaged abolitionist, which is undoubtedly an important role that should be remembered, but that should not surpass the journalist